Sobre a formação de diminutivo do português brasileiro (Revista de Estudos da Linguagem, 1999)
Diminutive formations are very productive in BrazilianPortuguese (BP). There are two ways to derive diminutive formsout of nominal words (i.e. nouns and adjectives/adverbs): -inho(a)suffixation e -zinho(a) suffixation. The latter is attached at thestem with the thematic vowel (-a, -o, -e, which represent themorphological class in nominal words, like gender and number)and the former is attached at the stem without the thematic vowel.There are many divergences in the literature to explain thediminutive formations which are treated: i) as derivational suffixes;ii) as phonological words; iii) -inho suffixation as derivation,-zinho suffixation as (phonological) compounding, etc.In this paper, I will argue that diminutive formation inBrazilian Portuguese (BP) is treated differently from the derivation/compound formation and the inflection in the process of wordformation – that is, diminutive formation has independent status.